Level of Students’ Motivation in Using Quizizz Based on Pintrich's Theory - Ramadhani, Khori Putri; Adrefiza, Adrefiza; Sukarno, Berliana Sukma Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the level of students' motivation in the motivation subcomponents of Students in the academic year 2021. In this descriptive study, the researchers used a questionnaire to collect data. The sample of this research is called total sampling, which had 96 students of English education and English non-education study programs at Universitas Negeri Padang (N=96). The findings of the data analysis showed that most of the levels of students’ motivation are high in each of the subcomponents based on Pintrich's theory. The subcomponents of motivation that scored the highest were Intrinsic Goal Orientation (4.3), Extrinsic Goal Orientation (4.2), Control of Learning Beliefs (4.1), Task Value and Self-Efficacy for Learning and Performance (both 3.9), and Test Anxiety (3.8). Therefore, the English students in the Universitas Negeri Padang have high-level motivations based on Pintrich's theory. For the next study, it can be found the attitude of students in using Quizizz